(untitled) (Perioperaciina Medicina, 2023)
Meckel’s diverticulum is the most common congenital anomaly within the gastrointestinal tract, with a prevalence in the general population of 0.9–3 %. Among the malignant neoplasms associated with Meckel’s diverticulum, carcinoids and gastrointestinal stromal tumors predominate in percentage, with adenocarcinomas accounting for less than 6% of all associated malignancies. The authors present a rare case report of a 67-year-old patient with gastric-type adenocarcinoma in Meckel’s diverticulum, with metastatic foci in both lobes of the liver at the time of diagnosis. The case demonstrates diagnostic and therapeutic procedures that led to a correct diagnosis and a satisfactory treatment outcome. They emphasize the importance of using all the possibilities of diagnosis and treatment as well as the necessity of cooperation with other experts in the proper management of this disease, they express an opinion about considering prophylactic resection of intraoperatively detected Meckel’s diverticulum.